Molecular construction of bionanoparticles - Costa, Maria J. L. (2015)
VLPs (virus-like particles) are promising delivery vectors for molecular therapy, since they combine the major advantages of viral vectors with significantly fewer viral vector disadvantages. The present paper describes the molecular construction of chima